A comprehensive two-phase flow model for unidirectional sheet-flows. Issue 1 (2nd January 2018) - Chauchat, Julien
ABSTRACT: In this paper a comprehensive one-dimensional two-phase flow model for sediment transport under sheet-flow conditions is presented. The model is based on the dense granular flow rheology for the intergranular stresses and on a mixing length model for the Reynolds shear stress. A drift velocity model is introduced to represent the vertical dispersion effects. Recent experimental data are used to improve the mixing length model and the numerical model is validated for four configurations. The model is further assessed by comparing the dependence of the sediment transport rate and the sheet layer thickness on the Shields number. The good agreement with experimental data confirms the capability of the model formulation to reproduce unidirectional sheet-flows. The agreement with the latest kinetic theory of granular flows based model demonstrate that the dense granular flow rheology can be used as an alternative approach to kinetic theory in two-phase flow models.